U.S. Army hand-to-hand combat handbook (Lyons Press, 2010)
This book is the twenty-first century hand-to-hand combat field manual the U.S. Army distributes to all its soldiers. It presents all the essential skills in one durable package--how to ground-fight, throw and take down the enemy, strike the enemy, use handheld weapons, and defend yourself. Proficiency in hand-to-hand combat is one of the fundamental building blocks for training the modern soldier. Soldiers must be prepared to use different levels of force in an environment where conflict may change from low intensity to high intensity over a matter of hours; and many militarynoperations, such as peacekeeping missions or noncombatant evacuation, may restrict the use of deadly weapons. Hand-to-hand combat training can save lives when unexpected confrontations occur.